茎突综合征与缺血性卒中：罕见但必须重视的病因（Styloid Process Syndrome and Ischemic Stroke: A Rare but Important Cause） - 石艳萍，罗颜，朱龙海，时代，曹勇军，石际俊（SHI Yanping, LUO Yan, ZHU Longhai, SHI Dai, CAO Yongjun, SHI Jijun） (Zhongguo cuzhong zazhi, 2025)
茎突综合征可导致骨源性缺血性卒中，是一种罕见的脑血管病病因，由其引起的颈动脉夹层易被漏诊和误诊。本文通过分析现有文献，综述了茎突综合征与缺血性卒中的关系，探讨了茎突综合征的解剖学基础、流行病学特征、引起脑血管病的病理机制及相关的诊断和治疗，旨在提高临床医师对茎突综合征引起缺血性卒中的认识，为临床诊治工作提供参考。Abstract: Styloid process syndrome can lead to bone-derived ischemic stroke and represents a rare etiology of cerebrovascular disease. Carotid dissection caused by it is prone to being underdiagnosed and misdiagnosed. This article reviews the relationship between styloid process syndrome and ischemic stroke by analyzing existing literature and discussing the anatomical basis, epidemiological characteristics, pathological mechanisms of inducing cerebrovascular disease, and relevant diagnosis and treatment of styloid process syndrome. It aims to enhance clinicians’ understanding of ischemic stroke caused by styloid process syndrome and to provide a reference for clinical diagnosis and treatment.